An Investigation on Vibration Welding of Amorphous and Semicrystalline Polymers. Issue 3 (17th February 2016) - Pal, Kaushik; Panwar, Vinay; Friedrich, Sven; Gehde, Michael
Abstract : Vibration welding technique has been used to study the weld zone of thermoplastic polymers using ABS (amorphous), PC (amorphous), PMMA (amorphous), and PBT (semicrystalline). Polymers were welded using alike components and combinations of semicrystalline polymer with different amorphous polymers. Mechanical testing of welded polymers has proved that the tensile strength, elongation at break, and deformation was highest for PC–PC weld and least for ABS–ABS weld, when alike polymers were welded. However, welding of semicrystalline and amorphous polymer shows enormous reduction in its tensile strength as well as other tensile properties. Also, the tensile fracture of PBT with other amorphous polymers always occurred at weld zone which was not always in case of alike polymer welds. The weld strength of these polymers was observed to be dependent on the mechanical interlocking among the layers and not on interfacial bonding. This phenomenon may be due to the difference in glass transition temperatures of semicrystalline and amorphous polymers. XRD, FESEM, and AFM have been used in this study to observe the morphology of welded surfaces.